(untitled) (Indian Journal of Child Health, 2018)
Introduction: Hemoglobinopathies are the common genetic disorders and are considered as the emerging health burden. To reduce the childhood and infant mortality and morbidity, early recognition by newborn screening and timely intervention is necessary. Objectives: The objectives of this study are to evaluate the prevalence of different hemoglobinopathies in the study population and to compare the efficacy of isoelectric focusing (IEF) and high-performance liquid chromatography (HPLC) tests in the neonatal screening for hemoglobinopathies. We have also assessed the predominant mutations for all ?-thalassemia variants. Materials and Methods: The prospective observational study was conducted in the Department of Pathology in collaboration with the Department of Neonatology over 1½ years including 4200 neonates. Both IEF and HPLC diagnoses were attempted and compared with recall HPLC and parent HPLC. DNA analysis was also done further confirmation in all thalassemia cases. Results: A total of 213 cases with 11 Hb variants were detected; among them, HbE trait was the most prevalent type. Overall sensitivity, specificity, and negative and positive predictive values were noted. The results of IEF were comparable with HPLC with a statistically significant measure of agreement of ?=0.928 between the two. DNA analysis of 37 ?-thalassemia variants revealed three common mutations, i.e., cd26 (G>A), IVS1-5 (G>C), and cd15 (G>A). Conclusion: In IEF, the hemoglobin separation is very precise with little band overlap, but the process and interpretation need a high expertise. Due to more sensitivity, IEF should be the initial screening test followed by recall HPLC for confirmation of the diagnosis.